Magnetically recoverable magnetite-reduced graphene oxide as a demulsifier for surfactant stabilized crude oil-in-water emulsion - Cozzoli, P. Davide; Yau, Xin Hui; Khe, Cheng Seong; Mohamed Saheed, Mohamed Shuaib; Lai, Chin Wei; You, Kok Yeow; Tan, Wai Kian (Public Library of Science, 2020)
Oily wastewater, especially water-oil emulsion has become serious environmental issue and received global attention. Chemical demulsifiers are widely used to treat oil-water emulsion, but the toxicity, non-recyclable and non-environmental friendly characteristic of chemical demulsifiers had limited their practical application in oil-water separation. Therefore, it is imperative to develop an efficient, simple, eco-friendly and recyclable demulsifiers for breaking up the emulsions from the oily wastewater. In this study, a magnetic demulsifier, magnetite-reduced graphene oxide (M-rGO) nanocomposites were proposed as a recyclable demulsifier to break up the surfactant stabilized crude oil-in-water (O/W) emulsion. M-rGO nanocomposites were prepared via in situ chemical synthesis by using only one type Fe salt and GO solid as precursor at room temperature. The prepared composites were fully characterized by various techniques. The effect of demulsifier dosage and pH of emulsion on demulsification efficiency (ED) has been studied in detailed. The demulsification mechanism was also proposed in this study. Results showed that M-rGO nanocomposites were able to demulsify crude O/W emulsion. The ED reaches 99.48% when 0.050 wt.% of M-rGO nanocomposites were added to crude O/W emulsion (pH = 4). Besides, M-rGO nanocomposites can be recycled up to 7 cycles without showing a significant change in terms of ED. Thus, M-rGO nanocomposite is a promising demulsifier for surfactant stabilized crude O/W emulsion. © 2020 Yau et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.